EXPLORATION ON THE TEACHING REFORM OF “X-Y THEORY” IN THE DESIGN COURSE OF ENVIRONMENTAL DESIGN SPECIALTY BASED ON EMOTION REGULATION - Ma, Xina; Wang, Mengyao; Xin, Kai (The international journal of neuropsychopharmacology, 2022)
Abstract Background In view of the new era of teaching reform, the teaching mode of colleges and universities has changed the concept of education and innovative talent training mode, it is emphasized that “curriculum is the core element of talent training, and the quality of curriculum directly determines the quality of students.” talent training has different levels of teaching reform and curriculum practice. In response to this demand, colleges and universities have also carried out different degrees of teaching reform and curriculum practice research. Especially in the design curriculum of environmental design specialty, it is very necessary to explore the teaching reform of “X-Y theory” based on emotional regulation. Research Objects and Methods In order to overcome the shortcomings of this course in knowledge dimension, scalability, design thinking development and regional industry, this course is based on McGregor's “X-Y theory”, that is, psychological behavior motivation. According to the principle of street design, the basic theory and experimental test of street microclimate environment, guide students to carry out the simulation design practice of street landscape design. Each stage of the design practice process starts from the students' emotional “sensory multi-channel”, through the students' good sensory channel to obtain and remember matching information, and test the students' sensitivity and understanding of knowledge points. The second knowledge integration test is conducted through online sharing evaluation and offline simulated defense courses, so that students can promote each other and gradually improve in their autonomous learning experience. Use students' painting materials to establish a course case base. In order to verify the influence of the teaching reform exploration of the design course X-Y theory of environmental design specialty on emotion regulation, this study measured the junior middle school students in a school in a northern city, half male and half female, aged between 13 and 16 years (average age is 14.96 ± 0.85 years). According to the scores of “cognitive reappraisal” and “expression inhibition” strategies, the subjects were divided into high and low groups, and those with significant differences in the scores of the two strategies were selected as the subjects of the experimental group. According to the scores of “cognitive reappraisal” and “expression inhibition”, 50% of the middle group was used as the subjects of the control group. Finally, there were 100 effective subjects, including 50 in the positive emotion group and 50 in the negative emotion group. Using emotion inducing materials, negative emotion inducing materials are a 10 minutes film clip of “Tangshan earthquake”. The film describes the story that when the earthquake occurred, the family was buried underground, and the mother struggled to make the decision that two children can only save one child in order to save her children. The positive emotion inducing material selects a 6-minute film clip of “people in the middle of nowhere”, which tells a series of funny things that happen when two men live in a small hotel together. Neutral emotion inducing material selects a scenic film as the film material of educational film. Results Through online theoretical lectures, preliminary research, surveying and mapping research, microclimate measurement, practical design exercises and expert simulation debate, students deepen their understanding and understanding of the physical characteristics of street space and the actual construction of engineering technology through repeated matching and intentional matching strategies, so as to realize the balanced development of students' psychological function in all aspects. The results of repeated measurement analysis of variance showed that after watching the negative emotion induced film, the scores of negative emotion words (sadness, pain, fear, etc.) were significantly higher than the pre-test scores, and the scores of positive emotion words (happiness, interest) were significantly lower. This shows that the negative emotion inducing film clips effectively induce the subjects' negative emotion, and the selection of negative emotion inducing materials is reasonable. After watching the positive emotion induced film, the scores of positive emotion words (happiness and interest) were significantly higher than the pre-test scores, and the scores of negative emotion words (surprise and fear) decreased significantly, and there was no difference between the negative emotions (anger, disgust, sadness, contempt, embarrassment and pain) caused by the two videos. This shows that the positive emotion inducing film can effectively induce the subjects' positive emotion, and the selection of positive emotion experimental materials is reasonable. The level of optimism has a significant inhibitory and influence on the level of self depression, at the level of 0.01. Conclusion This course aims to meet students' different needs and stimulate students' autonomous learning potential through four different application experience modes: integration, integration, creation and enjoyment. From the curriculum feedback in the past three years, the intentional mismatch strategy selection of students' behavior path can be extended to allow students to experience and evaluate problem conflicts by evaluating courses, such as mapping, studying and testing real cases. This teaching method can effectively promote the depth and breadth of the teaching mode reform of architectural background design course, and is conducive to the formation of more practical teaching effect in the course. Acknowledgements Supported by a project grant from The Second Batch of New Engineering Research and Practice Project of the Ministry of Education (Project No. B-TMJZSLHY20202152).